Monitoring the Future: A Continuing Study of the Lifestyles and Values of Youth, 1977 - Johnston, Lloyd D. ([Verlag nicht ermittelbar], 1984)
This is the third annual survey in this series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. The students are randomly assigned one of five questionnaires, each with a different subset of topical questions but all containing a set of "core" questions on demographics and drug use. There are about 1,300 variables across the questionnaires. Full details on the research design and procedures, sampling methodology, content areas, and questionnaire design, as well as percentage distributions by respondent's sex, race, region, college plans, and drug use, appear in the annual Institute for Social Research volumes MONITORING THE FUTURE: QUESTIONNAIRE RESPONSES FROM THE NATION'S HIGH SCHOOL SENIORS.